Government Legal Responsibility from a Human Rights Perspective in the Health Sector - Dwi Prakoso, Agung; Sara, Rineke; Barthos, Megawati (Riviera Publishing, 2024)
Ensuring health for the community in receiving quality and adequate medical services as a basic right is the government's responsibility, which is regulated in Article 28H of the 1945 Constitution and Law Number 36 of 2009 concerning Health. The government is obliged to fulfill the public's right to health in accordance with its capabilities and resources, and must not limit or hinder the public's access to adequate health services. This research aims to protect people's rights to medical services that are supported through legal protection. This research uses a normative legal approach and uses secondary data sourced from laws, journals and analytical descriptive articles. The results of this research are used to gain deeper insight into health problems, determine them, and then proceed with scientific solutions in accordance with Law no. 39 of 1999 concerning Human Rights and Law no. 36 of 2009 concerning health. It is stated that the people's right to health is a human right for all human beings that must be fought for. The 2014 law establishes health service standards as an instrument of a legal system based on the principle of the supremacy of law to ensure compliance with health regulations as well as human rights.